2002
DOI: 10.1103/physrevb.65.174104
|View full text |Cite
|
Sign up to set email alerts
|

Theory ofAl2O3incorporation in

Abstract: Different possible forms of Al 2 O 3 units in a SiO 2 network are studied theoretically within the framework of density-functional theory. Total-energy differences between the various configurations are obtained, and simple thermodynamical arguments are used to provide an estimate of their relative importance at different Al concentrations. Some experimentally accessible quantities ͑hyperfine parameters, electric-field gradient tensors, and core-level chemical shifts͒ are derived, and compared with experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 53 publications
3
27
0
Order By: Relevance
“…Therefore, he pointed out that the contribution of entropy is inevitable to explain the ErAl codoping effect; i.e., the Al codoping increases ¦S mix . 76) This idea is compatible with the fact that the incorporated Al 3+ ion behaves as a network modifier; i.e., the coordination number is 6. It should be noted that the coordination number of Al in SiO 2 depends on its concentration; i.e., if the Al 2 O 3 content is high, the 6-fold coordination is dominant, but the 4-fold coordination is found in the very low concentration (ppm level).…”
Section: Mechanism Of Codoping Effectsupporting
confidence: 53%
See 1 more Smart Citation
“…Therefore, he pointed out that the contribution of entropy is inevitable to explain the ErAl codoping effect; i.e., the Al codoping increases ¦S mix . 76) This idea is compatible with the fact that the incorporated Al 3+ ion behaves as a network modifier; i.e., the coordination number is 6. It should be noted that the coordination number of Al in SiO 2 depends on its concentration; i.e., if the Al 2 O 3 content is high, the 6-fold coordination is dominant, but the 4-fold coordination is found in the very low concentration (ppm level).…”
Section: Mechanism Of Codoping Effectsupporting
confidence: 53%
“…Their results indicated that the oxygen coordination number of Al is primarily 6, and the number of AlO 6 unit surrounding an Er is 1. Laegsgaard 76) calculated the formation energy of ¡-quartz supercell composed of 24 TO 4 units (T=Al and Si) including M 3+ ions (M=Er or Al) at the center of a sixmembered ring. The formation energy of the supercell including an ErAl complex (ErAl 3 O 6 ) was larger than that including an ErEr cluster (Er 2 Si 2 O 7 ) and an AlAl cluster (Al 4 O 6 ).…”
Section: Mechanism Of Codoping Effectmentioning
confidence: 99%
“…I shall denote this structure ͓Al 4 O 6 ͔. In calculations which will be detailed in a separate paper 7 I have found that this is indeed a likely geometry for Al ions in silica at concentrations above 0.1%. However, in the case of interstitial Al, the structures schematically depicted in Figs.…”
Section: Theoretical Approachmentioning
confidence: 97%
“…As follows from XAFS experiments, the pair-correlation function has maxima at R 1 = 3 5 Å and R 2 = 3 9 Å, whereas it takes approximately a constant value for R > 4 5 Å [10]. It was found also that suppression of the short-range order leads to improved characteristics of high concentration erbium doped fibre amplifiers and lasers and can be realized by increasing the solubility of erbium in host matrix (codoping by Al [11] or using phosphate glass [12]) or by modification of deposition process (Direct Nanoparticle Deposition [13]). Application of such fibres as an active media for HC EDFLs resulted in auto-oscillations with two characteristic frequencies of about 10 kHz and 100 kHz and two threshold pump powers.…”
Section: Introductionmentioning
confidence: 90%